Formal carbene insertion into CO double bond: A facile approach to the synthesis of 2H-chromenes. Issue 35 (30th August 2018) - Li, Mingfeng; Chu, Rui; Zhao, Yun; Hu, Wenhao; Liu, Shunying
Abstract: A formal carbene insertion into CO double bonds of 2-hydroxycinnamaldehydes catalyzed by Rh2 (esp)2 with Na2 CO3 as additive has been disclosed by using aryldiazoacetates as carbene precursors. 2 H -chromenes with a quaternary carbon at C-2 position were readily obtained from simple starting materials in good yields with excellent diastereoselectivity under mild reaction conditions in one pot. The reaction mechanism was investigated and proposed as the formation of epoxide intermediate from Rh(II)-associated carbene and ( E )-2-hydroxycinnamaldehyde and followed by a cascade epoxide ring-opening procedure in which the ( E )-intermediate was converted into the ( Z )-intermediate to give ( Z )-products. Graphical abstract: